Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Turnover Intention (Studi pada Fasilitator SLRT Dinas Sosial Kabupaten Kolaka) - Nurfadillah Lubis; Suwarto Suwarto; Ismanto Ismanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The study aims to analyze the effect of financial literacy and financial attitude on financial management owned by students. The research method used in this study was the student of Management study Program Faculty of Social and Politic University of Sembilanbelas November Kolaka (USN Kolaka). In the even semester 2019-2020. There were 225 student. The sampleused in this study amounted to 140 students using random sampling technique. The data used in this study are primary data. Namely by distributing questionnarres. The data analysis technique used in this study regarding financial literacy and financial attitude shown that both has a significant positive influence on financial management practices with a t-statistic value of 3,923 and p-value of 0,000 for financial literacy and financial attitude variable is posit ive with a t-statistic value of 4,074 and p-value 0,000.